2017
DOI: 10.2147/lra.s138998
|View full text |Cite
|
Sign up to set email alerts
|

Great auricular neuropraxia with beach chair position

Abstract: Shoulder arthroscopy has been shown to be the procedure of choice for many diagnostic and therapeutic interventions. Neuropraxia of the great auricular nerve (GAN) is an uncommon complication of shoulder surgery, with the patient in the beach chair position. We report a case of great auricular neuropraxia associated with direct compression by a horseshoe headrest, used in routine positioning for uncomplicated shoulder surgery. In this case, an arthroscopic approach was taken, under regional anesthesia with sed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“… 7 , 13 , 21 Neuropraxias of the greater auricular, lesser occipital nerves, and hypoglossal nerves have been described as a sequelae of rotation and traction of the head and neck during beach chair positioning, direct pressure on nerves via headrest equipment placement, and traction of the operative extremity during surgery. 9 , 12 , 15 , 17 , 19 In addition, placing additional padding or pillows between structures such as the abdominal pannus and the anterior thigh or the lateral knees and the bed is important to prevent compression on nearby structures such as the LFCN or common peroneal nerve. Diskina et al reported five cases of peroneal nerve palsy after beach chair positioned shoulder surgery, citing potentially contributing factors such as preexisting spinal pathology, taller patients, longer surgeries, and greater blood loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 7 , 13 , 21 Neuropraxias of the greater auricular, lesser occipital nerves, and hypoglossal nerves have been described as a sequelae of rotation and traction of the head and neck during beach chair positioning, direct pressure on nerves via headrest equipment placement, and traction of the operative extremity during surgery. 9 , 12 , 15 , 17 , 19 In addition, placing additional padding or pillows between structures such as the abdominal pannus and the anterior thigh or the lateral knees and the bed is important to prevent compression on nearby structures such as the LFCN or common peroneal nerve. Diskina et al reported five cases of peroneal nerve palsy after beach chair positioned shoulder surgery, citing potentially contributing factors such as preexisting spinal pathology, taller patients, longer surgeries, and greater blood loss.…”
Section: Discussionmentioning
confidence: 99%
“… 14 Nevertheless, while beach chair positioning affords advantages, complications have been reported including stroke, cervical radiculopathy, and peripheral nerve compressive neuropraxias, including lateral femoral cutaneous nerve (LFCN) palsy, brachial plexopathy, and common peroneal nerve palsy. 1 , 6 , 8 , 9 , 10 , 16 , 22 , 24 The authors present a unique case of transient bilateral sciatic nerve palsy following repair of a pectoralis major tendon tear in a collegiate offensive lineman. This represents the first report of a neurologic complication at this level in the literature.…”
mentioning
confidence: 99%
“…50 51 52 53 54 Eight cases of neurapraxia of the greater auricular nerve have been reported in the literature after shoulder surgery in the BC position, and direct nerve compression by the headrest was considered to be the etiology. 55 56 57 58…”
Section: Beach Chair Positionmentioning
confidence: 99%
“…The most well-known complication relates to the lowering of blood circulation to brain, however there have also been reports of other complications peripherally which include injuries to cornea, great auricular nerve and sciatic nerve to name a few [2,[4][5][6]. One major concern while sitting the patient up on beach-chair position is the rapidly altering position of the cervical spine.…”
Section: Introductionmentioning
confidence: 99%